Effects of Acupuncture in Ischemic Stroke Rehabilitation: A Randomized Controlled Trial - Li, Lixia; Zhu, Weifeng; Lin, Guohua; Chen, Chuyun; Tang, Donghui; Lin, Shiyu; Weng, Xiaorong; Xie, Liqin; Lu, Lihong; Li, Weilin (Frontiers in Neurology, 2022)
Background Acupuncture is a well-known treatment option for ischemic stroke recovery, but evidence of its effectiveness remains limited. This is a randomized controlled trial to evaluate the effectiveness of acupuncture treatment for ischemic stroke rehabilitation. Methods Rehabilitation training was provided to the control group. In acupuncture arm 1, these acupoints were derived from the ancient books, including GV20 (baihui), GV26 (shuigou), PC9 (zhongchong), ST6 (jiache), ST4 (dicang), LI15 (jianyu), LI11 (quchi), LI4 (hegu), GB30 (huantiao), GB31 (fengshi), GB34 (yanglingquan), and GB39 (xuanzhong). In acupuncture arm 2, the acupoints used were GV20 (baihui), PC6 (neiguan), LI11 (quchi), LI10 (shousanli), SJ5 (waiguan), LI4 (hegu), GB30 (huantiao), ST36 (zusanli), GB34 (yanglingquan), SP6 (sanyinjiao), ST41 (jiexi), and LR3 (taichong), which were extracted from Acupuncture and Moxibustion Science. After acupuncture, the needles were left in for 30 min and manually manipulated every 10 min. The three groups received treatment once a day, 5 times a week for 2 weeks. The primary outcome was the National Institutes of Health Stroke Scale (NIHSS), and the secondary outcomes were the Barthel Index (BI) and the Modified Ashworth Scale (MAS). Outcomes were measured in patients both before and after treatment. Results A total of 497 patients with ischemic stroke were randomized into either arm 1 (159 cases), arm 2 (173 cases), or the control group (165 cases). After 2 weeks of treatment, the NIHSS scores for arm 1 were lower than those of the control group (P = 0.017); the BI scores were higher in arm two than that in the control group at T2 (P = 0.016) and follow-up (P = 0.020). Additionally, there was no significant difference between arm one and the control group for either the BI scores or the MAS scores (P > 0.05) and no significant difference between arm two and the control group for the MAS scores or the NIHSS scores (P > 0.05). Conclusion The clinical efficacy of arm 1 and arm 2 (acupuncture groups) was superior to that of the control group, but there was no difference between the effects of the two acupuncture groups. Clinical Trial Registration http://www.chictr.org.cn/index.aspx, identifier: ChiCTR-IOR-16008627.